RNA-binding proteins involved in post-transcriptional regulation in bacteria - Van Assche, Elke; Van Puyvelde, Sandra; Vanderleyden, Jos; Steenackers, Hans P. (Frontiers in Microbiology, 2015)
Post-transcriptional regulation is a very important mechanism to control gene expression in changing environments. In the past decade, a lot of interest has been directed towards the role of small RNAs in bacterial post-transcriptional regulation. However, small RNAs are not the only molecules controlling gene expression at this level, RNA-binding proteins play an important role as well. CsrA and Hfq are the two best studied bacterial proteins of this type, but recently, additional proteins involved in post-transcriptional control have been identified. This review focuses on the general working mechanisms of post-transcriptionally active RNA-binding proteins, which include (i) adaptation of the susceptibility of mRNAs and sRNAs to RNases, (ii) modulating the accessibility of the ribosome binding site of mRNAs, (iii) recruiting and assisting in the interaction of mRNAs with other molecules and (iv) regulating transcription terminator / antiterminator formation, and gives an overview of both the well-studied and the newly identified proteins that are involved in post-transcriptional regulatory processes. Additionally, the post-transcriptional mechanisms by which the expression or the activity of these proteins is regulated, are described. For many of the newly identified proteins, however, mechanistic questions remain. Most likely, more post-transcriptionally active proteins will be identified in the future.